(3GdLGeYs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s ((3ehSi Hf GHQGgje s)
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B( (3abVGgf SHY SehGJ ai jhejf hGhMi ai cd SeGA GeQgG (B) (3GdGjI ef ShQI Me GdSLOI s
(3BNQgG (B:s
(3jfJgi HJaSjQ BNQ ShQI GdWhQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B456 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B534s
Keywords: (3GdJaSjQ hYdhe GdbQBfs